Autophagy-mediated NKG2D internalization impairs NK cell function and exacerbates radiation pneumonitis - Wang, Ruiqing; Ma, Xinyue; Zhang, Xinyu; Jiang, Dizhi; Mao, Hongyuan; Li, Zerun; Tian, Yu; Cheng, Bo (Frontiers in Immunology, 2023)
Radiation pneumonitis, a major side effect limiting the clinical application of radiation therapy for thoracic tumors, severely affects patients' survival through respiratory distress and lung function failure. Natural killer (NK) cells play significant roles in inflammatory diseases, yet their roles in radiation pneumonitis remain elusive.Here, we observed an increase in NK cell infiltration in radiation pneumonitis, but their functionality was notably suppressed. Based on animal models of radiation pneumonitis, we propose that the activation of NK cell function significantly slows the progression of radiation pneumonitis. Further investigation revealed that CXCL10 and ROS levels significantly increase during disease progression. CXCL10 promotes infiltration by activating the CXCR3 receptor on NK cells, while immunofluorescence staining and Western blotting showed that autophagy in NK cells from radiation pneumonitis patients is overly activated and associated with ROS accumulation.Additionally, through immunoprecipitation, we found that the binding of NKG2D to adaptor proteins AP2, LC3, and lysosomes increased post-radiation, promoting the endocytosis of the NKG2D receptor on the cell surface, leading to its degradation via the lysosomal pathway. Inhibiting autophagy significantly enhances NKG2D expression and restores NK cell function. In conclusion, these findings suggest that radiation-induced lung injury suppresses NK cell function via an autophagy-dependent pathway, and targeting autophagy and NK cells may provide new therapeutic options for radiation pneumonitis.